Teknik Vokal Frasering Dalam Menyanyikan Lagu Arise And Shine Forth Karya Sally DeFord - Rosenni Situmorang; Robert K.A Simangunsong; Diana Situmeang; Monang Asi Sianturi; Lince Rauli Ture Simamora (Jurnal Pendidikan Agama dan Teologi, 2024)
The aim of this research is to find out vocal phrasing techniques for good and correct sentence fragments in singing the song Arise And Shine Forth. This research uses qualitative research methods using observation, interviews and documentation. This research was carried out by collecting information through field research to obtain results which were processed into accurate data. The research process carried out as data collection is: videos and interviews. By singing the song Arise And Shine Forth, the author uses accompaniment via digital media, namely karaoke. The research results show that the process of implementing the vocal phrasing technique training in singing the song Arise And Shine Forth, namely practicing body posture, breathing, articulation and learning the phrasing of the song Arise And Shine Forth. In the score for the song Arise And Shine Forth, it is known that the chord is 4/4, 42 bars and tempo 68 (Adagio), the tempo tends to be slow but tends to be relaxed. This song is performed in a duet consisting of a man and a woman using different voice melodies. In bars 6 to 10 it is sung by women. Bars 12 to 14 are sung by men. Bars 18 to bar 28, the lyrics are sung together using different melodies. From all the observations and methods that the author has used while conducting research, the vocal phrasing technique in singing the song Arise And Shine Forth is very important. To obtain good and correct phrasing techniques for phrasing sentences, you need to practice and master good vocal techniques to be able to sing the song. There are several ways that must be considered to master good phrasing techniques, namely: practicing breathing, understanding the song being sung, understanding the purpose or message of a song and looking at the sentences in the song where they are divided.